KAIDAH INTERAKTIF PENGEMBANGAN MODUL ELEKTRONIK PEMBELAJARAN FISIKA BERBASIS LCDS PADA MATERI GERAK MELINGKAR - Rini Budiharti; Pujayanto Pujayanto; Ahmad Fauzi; Istiqomah Nugraheny (Universitas Sebelas Maret, 2019)
This article aims to describe the interactive rules of the development of LCDS-based electronic physics learning modules on Circular Motion material.The research method used is the development method with the ADDIE model. In this case, it only covers three stages, namely the Analysis, Design, and Development stage. The data obtained are qualitative data supported by quantitative data.The data source consisted of the results of the validation of 2 expert validators, 3 reviewers of high school physics teachers and the results of the students' assessment during the trial.There are three stages of the trial: one-to-one trials involving 3 students, small-group trials involving 9 students, and field trials involving 89 students. All trials were conducted at 3 different schools: SMA Al Islam 1 Surakarta, SMA N Kebak Kramat Karanganyar dan SMA N Colomadu Karanganyar. The data analysis technique used is descriptive qualitative supported by quantitative data. Based on the results of validation and testing, it shows that the LCDS-based physics electronic module that is developed meets the criteria very well.The interactive rules of developing this module can be observed from the module's storyboard. The storyboard analysis shows that in each sub-program, the content structure of the module consists of an introduction (in the form of video shows, followed by questions to explore students' initial understanding), simulations supported by LKPD (means of learning students), discussion forums, material summaries (reinforcement of discussion results) , practice questions, and evaluation questions (evaluating student understanding).Overall it can be concluded that the results of the development of LCDS-based physics learning modules on Circular Motion material meet the criteria very well, from the results of the storyboard analysis the module shows that the module can support interactive learning.